2017
DOI: 10.1186/s13052-017-0426-0
|View full text |Cite
|
Sign up to set email alerts
|

The involvement of musculoskeletal system and its influence on postural stability in children and young adults with cystic fibrosis

Abstract: BackgroundCystic fibrosis (CF) affects the musculoskeletal system via a multifactorial pathway that includes vitamin D deficiency and involvement of respiratory muscles such as intercostals due to recurrent upper and lower respiratory tract infections. Eventual result is the deterioration of musculoskeletal health and posture in CF patients. Postural stability is directly affected by posture and can be compromised in every musculoskeletal problem. The aim of this study is to evaluate musculoskeletal system and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 22 publications
(22 reference statements)
1
5
0
Order By: Relevance
“…Interestingly in our study, patients with spinal and/or joint pain were significantly shorter (167 ± 7 vs. 172 ± 9 cm, p = 0.023) and more frequently colonized with Staphylococcus aureus (91% vs. 56%, p < 0.008). The comparison is difficult with other specific studies concerning musculoskeletal and arthropathy in CF (6,13,36,37). In Roehmel et al study involving 186 CF children and adults (mean age: 27 years), patients with CFA (defined as at least one symptom out of the following: joint pain, joint swelling, joint reddening or limitation of movement) were more likely to be older, female gender, and to have a higher rate of total IgG, chronic colonization with Aspergillus spp.…”
Section: Discussionmentioning
confidence: 95%
“…Interestingly in our study, patients with spinal and/or joint pain were significantly shorter (167 ± 7 vs. 172 ± 9 cm, p = 0.023) and more frequently colonized with Staphylococcus aureus (91% vs. 56%, p < 0.008). The comparison is difficult with other specific studies concerning musculoskeletal and arthropathy in CF (6,13,36,37). In Roehmel et al study involving 186 CF children and adults (mean age: 27 years), patients with CFA (defined as at least one symptom out of the following: joint pain, joint swelling, joint reddening or limitation of movement) were more likely to be older, female gender, and to have a higher rate of total IgG, chronic colonization with Aspergillus spp.…”
Section: Discussionmentioning
confidence: 95%
“…Of note, the differences between BPXR lung volumes and reference lung volumes were more marked with age (namely in subjects with lower postural compensation capacity) and particularly so for maximal expiration (that threatens balance more than maximal inspiration, see above). This postulated mechanism (impact of limited postural compensation capabilities on vital capacity) could, beyond aging, be called on to explain part of the impact of thoracic deformities on lung volumes [e.g., scoliosis (Szopa and Domagalska-Szopa, 2017) or secondary spinal lesions (Kenis-Coskun et al, 2017)].…”
Section: Discussionmentioning
confidence: 99%
“…40 Another study stated that children and young adults with CF had more frequent spinal and lower extremity deformities. 41 Lopes et al showed that children with persistent asthma had higher protraction of the head and shoulder. 42 Low body weight and bone mineralization, increased dyspnea and cough frequency, decreased peripheral muscle strength and pulmonary function, and shortening of the accessory respiratory muscles may contribute to postural abnormalities in patients with PCD.…”
Section: Resultsmentioning
confidence: 99%